ANALYSIS OF SOCIO-CULTURAL AND ENVIRONMENTAL ASPECTS OF THE FUNCTIONING OF INDUSTRIAL ENTERPRISES IN THE CONDITIONS OF UNITED TERRITORIAL COMMUNITIES IN UKRAINE - HAHALIUK, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the results of the analysis of socio-cultural and ecological components, defines the main features of these components of sustainable development of the studied industrial enterprises as a whole. A study of the main indicators that determine and reflect the socio-cultural component of the implementation of the germinal development of industrial enterprises of the Ternopil Region was carried out. The negative dynamics of the decrease in the share of profit oriented towards the social needs of both the workers of industrial enterprises and the community they represent are highlighted. An increase in labor productivity was noted at all the investigated enterprises. An analysis of the ecological component was carried out. The criteria that must be used when developing a strategy for the sustainable development of an industrial enterprise are described, and this will allow preserving the environment for future generations, and will not worsen the environmental conditions around the enterprise itself. It was determined that the basis of the current germinative development of industrial enterprises should be the protection and rational treatment of the environment. It was emphasized that it is necessary to solve the most painful problems, namely: pollution of air, water, and soil. The world experience of industrial entrepreneurship, which offers the basis of ways in the field of solid household waste management, is described. Having studied the socio-cultural and ecological components, it should be noted that the main threats in the future may be: an increase in the level of inflation, a decrease in wages for employees of an industrial enterprise, the destruction of socio-cultural infrastructure and environmental pollution due to the military invasion of the Russian Federation in Ukraine. In general, negative trends require the implementation of the concept of strategizing actions focused on strengthening the main components of the German development of these industrial enterprises.
Keywords: germinative development; industrial enterprise; sociocultural component; ecological component; functioning; Sustainability; employee